Explainer: Britain’s proxy war on Russia - CURTIS, MARK (Declassified Media Ltd, 2022)
UK participation in the Ukraine conflict is far-reaching, involving military and intelligence support, arms supplies and information warfare. But as Ukraine makes gains on the battlefield, Whitehall sees the war not only as a way to defend Kyiv but to ensure the strategic defeat of its rival, Russia - a dangerous strategy.